Immediate post‐resection diabetes mellitus after pancreaticoduodenectomy: incidence and risk factors. Issue 3 (10th September 2012) - Ferrara, Michael J.; Lohse, Christine; Kudva, Yogish C.; Farnell, Michael B.; Que, Florencia G.; Reid‐Lombardo, Kaye M.; Donohue, John H.; Nagorney, David M.; Chari, Suresh T.; Vege, Santhi S.; Kendrick, Michael L.
Abstract Background: New‐onset diabetes mellitus after a pancreaticoduodenectomy (PD) remains poorly defined. The aim of this study was to define the incidence and predictive factors of immediate post‐resection diabetes mellitus (iPRDM). Methods: Retrospective review of patients undergoing PD from January 2004 through to July 2010. Immediate post‐resection diabetes mellitus was defined as diabetes requiring pharmacological treatment within 30 days post‐operatively. Logistic regression was conducted to identify factors predictive of iPRDM. Results: Of 778 patients undergoing PD, 214 were excluded owing to pre‐operative diabetes (n= 192), declined research authorization (n= 14) or death prior to hospital discharge (n= 8); the remaining 564 patients comprised the study population. iPRDM occurred in 22 patients (4%) who were more likely to be male, have pre‐operative glucose intolerance, or an increased creatinine, body mass index (BMI), pre‐operative glucose, operative time, tumour size or specimen length compared with patients without iPRDM (P < 0.05). On multivariate analysis, pre‐operative impaired glucose intolerance (P < 0.001), pre‐operative glucose ≥ 126 (P < 0.001) and specimen length (P= 0.002) were independent predictors of iPRDM. A predictive model using these three factors demonstrated a c‐index of 0.842. Discussion: New‐onset, post‐resection diabetes occurs in 4% of patients undergoing PD. Factors predictive of iPRDM include pre‐operative glucose intolerance, elevated pre‐operative glucose and increased specimen length. These data are important for patient education and predicting outcomes after PD.